Rare earth element systematics in boiled fluids from basalt-hosted geothermal systems. (1st January 2019) - Fowler, Andrew P.G.; Zierenberg, Robert A.; Reed, Mark H.; Palandri, James; Óskarsson, Finnbogi; Gunnarsson, Ingvi
Highlights: Boiled basalt-hosted geothermal fluids have lower REE than submarine hydrothermal fluids. REE are incorporated into well scale precipitates. Mineral precipitation and chloride complexation control aqueous REE concentrations in boiled geothermal fluids. Abstract: Hydrothermal processes that lead to REE fractionation and redistribution are important for understanding water-rock interactions in geothermal energy resources and mineral deposits, and for determining how submarine hydrothermal activity affects the composition of oceanic crust. Much previous work on REE transport and deposition has focused on submarine hydrothermal vents. We report REE concentrations in boiled fluids sampled from five subaerial, basalt-hosted geothermal fields, and explore controls on aqueous REE concentrations by ligand complexation and mineral supersaturation. Samples that boiled at pressures between 0.8 and 2.83 MPa were obtained from the Reykjanes, Svartsengi, Hellisheidi, and Nesjavellir geothermal systems in Iceland, and the Puna geothermal system in Hawaii. For comparison, we also report REE concentrations in hydrothermal fluids from the sediment hosted submarine Middle Valley hydrothermal system, which boiled at >250 MPa. The pH(25°C) values of the sampled subaerial geothermal fluids range from 3.94 to 6.77, and Cl concentrations range from near seawater (502 mmol/kg) to dilute (1.9 mmol/kg). La, Ce and Eu are the only REE present at levels above 5 picomole/kg (pmol/kg) in the boiled geothermal fluids; and there are notable CI chondrite normalized La and Eu anomalies in the saline fluids. REE concentrations in Middle Valley hydrothermal fluids fall within the typical range reported for submarine hydrothermal fluids and have around two orders of magnitude higher REE than the boiled subaerial geothermal fluids. Bulk samples of precipitates in pipes from the Reykjanes geothermal system have detectable REE, confirming that downhole fluids have lost REE during boiling and production of fluids for geothermal energy. Isenthalpic boiling models show that the proportions of La and Eu chloride complexes increase relative to other aqueous species as boiling progresses, attenuating the incorporation of La and Eu into precipitated well scale solids. Fluorapatite is calculated to precipitate on boiling of low pH and saline fluids and calcite is calculated to precipitate from dilute and near-neutral pH fluids, and these minerals likely sequester REE in boiled subaerial fluids. Submarine hydrothermal fluids are constrained to boiling at higher temperatures than subaerial geothermal fluids owing to pressure from overlying cold seawater, therefore secondary minerals and solids that incorporate REE are not extensively precipitated and REE concentrations in the fluids are higher.